The 2nd International Laayoune Forum on Biosaline Agriculture 2022
DOI: 10.3390/environsciproc2022016068
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Rice Genotypes Suitable for Aerobic Direct-Seeded Conditions

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…The lowest no. of tillers per hill was found in RNR 10754 (9). The results are in conformity with the findings of Anusha et al [11] that early vigour genotypes showed high crop growth rate during preanthesis period which is reflected as higher number of tillers in vigorous genotypes compared to less vigorous genotypes.…”
Section: Growth Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…The lowest no. of tillers per hill was found in RNR 10754 (9). The results are in conformity with the findings of Anusha et al [11] that early vigour genotypes showed high crop growth rate during preanthesis period which is reflected as higher number of tillers in vigorous genotypes compared to less vigorous genotypes.…”
Section: Growth Parameterssupporting
confidence: 91%
“…Teng et al[7] and Fauzi et al[8] also reported that heavier seeds produced higher seedling dry weight with higher leaf area resulting in faster canopy and higher photosynthetic activity and thereby have greater potential to compete with weeds under DDSR.The highest plant height was recorded in the variety WGL 915 (122.99 cm) and the variety RNR 15435 (121.72 cm) was found on par, while lowest plant height was found in WGL 962 (85.45 cm). Similar variation in plant height under direct sowing was observed by Goyal et al[9] and *,** represent significance at 0.05 and 0.01 levels probability respectively…”
supporting
confidence: 82%